2016
DOI: 10.4238/gmr.15038522
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenicity and antigenotoxicity of Aloe arborescens Miller and Aloe barbadensis Miller in Aspergillus nidulans and Wistar rats

Abstract: ABSTRACT. Medicinal plants such as Aloe arborescens Miller andAloe barbadensis Miller are used by the general population to treat various diseases. Therefore, the aim of this study was to evaluate the antimutagenicity of these two species using a methG1 system in Aspergillus nidulans and the comet assay in rats. The animals were treated with the plants at concentrations of 360 and 720 mg/kg body weight (1 and 2, respectively) by gavage for 14 days, followed by the administration of etoposide on treatment day 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Polyphenolic compound like curcumin in its modified and unmodified forms were found to attenuate the cisplatin-induced DNA damage (Mendonça et al, 2015). Other mechanisms of inhibition of genotoxic effect of mutagens are inhibition of genotoxic effect, inhibition of cell proliferation, and modulation of signal transduction (Berti et al, 2016). Contrarily, Anil et al (2015) reported that A. vera leaf extract did not decrease genotoxicity of urethane in the bone marrow cells of rats and mytomycin -C induced genotoxicity in human lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenolic compound like curcumin in its modified and unmodified forms were found to attenuate the cisplatin-induced DNA damage (Mendonça et al, 2015). Other mechanisms of inhibition of genotoxic effect of mutagens are inhibition of genotoxic effect, inhibition of cell proliferation, and modulation of signal transduction (Berti et al, 2016). Contrarily, Anil et al (2015) reported that A. vera leaf extract did not decrease genotoxicity of urethane in the bone marrow cells of rats and mytomycin -C induced genotoxicity in human lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Aloe arborescens Miller and Aloe barbadenesis Miller also known as Aloe vera (Linn.) have been reported for their beneficial medicinal values including antitumoral, antidiabetic and immune boosting activities (Berti et al, 2016;Guo & Mei, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ROS cause lipid peroxidation directly or indirectly through production of free radicals leading to genotoxic and clastogenic effects on bone marrow (6,(11)(12)(13). Recently, great attention has been focused to identify new antimutagenic and/or anticarcinogenic compounds through alternative pathways (14).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many studies have investigated compounds that are present in foods and plants, and that have antimutagenic and/or an anticarcinogenic potential (Kaur et al, 2005;Berti et al, 2016). Antimutagenics are products or processes that reduce the frequency of spontaneous or induced mutations occurring (Erdtmann, 2003).…”
Section: Introductionmentioning
confidence: 99%